Urbanization and Social Inequality: Challenges in Building Social Cohesion in a City-Based Environment - Mardikaningsih, Rahayu (Journal of Social Science Studies, 2021)
Urbanization has a significant impact on social life in cities, affecting social structures and interactions between residents. Urbanization offers economic opportunities and infrastructural advances, but it also exacerbates social inequalities, especially in terms of housing, job, and basic services. The social segregation that occurs in big cities, both by economic class and ethnicity, causes social fragmentation that affects social cohesion between residents. Unequal access to urban facilities exacerbates inter-group tensions, leading to reduced social interaction and decreased mutual trust. Changes in social structure due to urbanization require serious attention in terms of their impact on social integration and solidarity in urban communities. Through a literature review, this research analyzes how urbanization affects social inequality and social cohesion in big cities, focusing on social segregation, lifestyle changes, and access to basic services. This research also explores how these factors contribute to reducing or increasing social cohesion, as well as the implications for public policy. The findings of this research point to the importance of designing inclusive and equitable policies to create a more harmonious and fair urban society, where individuals can gain equal access to opportunities and resources.